Perforating the GORE® CARDIOFORM septal occluder and atrial septal defect occluder to gain access to the left atrium. Issue 6 (2nd April 2020) - Anderson, Jason H.; Adamson, Teagan; Migliati, Elton; Herlihy, Jennipher; Danieu, Pierrette; Daly, John; Allen, Carissa; Hua, Khoa; Inglessis, Ignacio
Abstract: Objective: Perforate the expanded polytetrafluoroethylene membrane of the GORE® CARDIOFORM Septal Occluder (GSO) and GORE® CARDIOFORM ASD Occluder (GCA) after implantation. Background: Percutaneous transseptal access to the left atrium is necessary for many structural and electrophysiological procedures. The potential need to access the left atrium may influence decision‐making for patent foramen ovale or atrial septal defect closure. Methods: Sixteen canines underwent implantation of equal number GSO or GCA devices. A transseptal crossing procedure was performed through the device 85 (±1) days postoccluder implantation. The crossing procedure was performed utilizing commercially available equipment: radiofrequency/SureFlex sheath and standard needle/Mullin's sheath. Progressive dilation of the perforation was performed to allow passage of a 12 French Mullin's sheath into the left atrium. Results: Left atrial access was achieved in all cases. Postmortem analysis demonstrated passage through both occluder discs in all radiofrequency/SureFlex sheath cases (4 GSO, 4 GCA) and half of the standard needle/Mullin's sheath cases (3 GSO, 1 GCA). The remaining standard needle/Mullin's sheath cases demonstrated perforation through the right atrial disc but passage around the septal aspect of the left atrial disc, thus not perforating the left atrial disc. No acute embolic complications from the procedure were observed. Conclusions: Left atrial access may be achieved through the GSO or GCA devices after implantation and endothelialization. The combination of a radiofrequency needle and steerable sheath provides benefit over a standard needle and Mullin's sheath in accomplishing passage through both occluder discs.